Can We Prevent Stillbirth? - Fouks, Yuval; Tschernichovsky, Roi; Greenberg, Ariel; Bak, Stella; Sinai, Noa Brzezinski; Shinar, Shiri (American Journal of Perinatology, 2020)
Objective This study aimed to identify the frequency of potentially preventable causes of stillbirth in a large heterogeneous population.Study Design This is a retrospective study of all stillbirth cases between January 2011 and December 2016 at a single tertiary medical center. Deliveries resulting from a nonviable fetus prior to 24 weeks of gestation, intrapartum fetal death, and incomplete stillbirth workup were excluded. Potentially preventable stillbirth was defined as that of a nonanomalous fetus that most likely resulted from one or more of the following: (1) placental-mediated complications, (2) postterm pregnancy, (3) monochorionicity-associated complications, (4) cholestasis of pregnancy, (5) preventable or treatable infections, and (6) isoimmunization.Results During the study period, 312 stillbirths were identified, 228 of which met the inclusion criteria. Of the 110 cases with a recognized cause, 47 (20.6%) were potentially preventable. The most common causes were placental-mediated complications and preventable or treatable infections, accounting for 75 and 9% of all potentially preventable causes, respectively. There were no recognizable maternal risk factors for potentially preventable stillbirth.Conclusion One-fifth of all causes of stillbirth are potentially preventable. Due to the significant contribution of placental-mediated complications to preventable stillbirth, close sonographic surveillance and timely delivery may decrease risk substantially.
Keywords: stillbirth; intrauterine; fetal death; stillbirth prevention; fetal pathology